Data Parallel C++: Programming Accelerated Systems Using C++ and SYCL, 2nd Edition - Reinders, James; Ashbaugh, Ben; Brodman, James; Kinsner, Michael; Pennycook, John; Tian, Xinmin (Apress, 2023)
This open access book enables C++ programmers to be at the forefront of this exciting and important development that is helping to push computing to new levels. --